Victims of Severe Intimate Partner Violence Are Left Without Advocacy Intervention in Primary Care Emergency Rooms: A Prospective Observational Study. Issue 15 (August 2021) - Hackenberg, Elisa A. M.; Sallinen, Ville; Handolin, Lauri; Koljonen, Virve
Intimate partner violence (IPV) is a common cause of musculoskeletal injury. Although serious injuries are relatively rare, IPV is one of the leading causes of homicide. IPV victims seeking help in health care are known to be at specific risk of re-abuse. Previous studies of IPV victims in emergency room (ER) settings have focused on injury patterns, but little is known about the violence behind bruises and fractures. The aim of this study was to examine how violence severity and known risk factors for lethal re-abuse in IPV victims attending ERs are associated with injury severity, different patient groups, and referral to advocacy services. This was a prospective, observational, multicenter study of 146 self-reporting IPV victims in two Level IV trauma centers in Helsinki from October 2012 to November 2013. In our sample, serious injuries were rare, but patients had typically suffered severe violence, and half had at least one risk factor for lethal re-abuse. Both sexes and all age groups were represented among the patient profiles, and 88% attended ERs outside common working hours. Only 19% were referred to advocacy, and severe violence or risk factors for lethal re-abuse did not affect prevalence of referrals. Our results show that IPV victims in primary care ERs have typically either experienced severe violence or are at serious risk of re-abuse and even death. The resulting injuries do not usually require medical aftercare, and victims typically present outside common working hours. In the absence of a clear follow-up protocol, most IPV victims are left without any advocacy intervention.